2011
DOI: 10.1021/jf201401j
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal Effect and Chemical Composition of the Volatile Oil from Bergenia ligulata

Abstract: The chemical composition of the volatile oil from roots of Bergenia ligulalta was analyzed by GC-MS. A total of 97 compounds were identified. (+)-(6S)-Parasorbic acid (1) (47.45%), isovaleric acid (6.25%), 1,8-cineole (4.24%), (Z)-asarone (3.50%), and terpinen-4-ol (2.96%) were the most prominent constituents. (+)-(6S)-Parasorbic acid (1) was isolated and characterized by spectroscopic data. This is the first report of the existence of (+)-(6S)-parasorbic acid in the saxifrage family. The volatile oil and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Monoterpenoids and sesquiterpenoids have been reported to possess biological activities against pests such as Tribolium castaneum , Lasioderma serricorne or Attagenus piceus . Although their mode of action has not been well studied, some experiments have demonstrated that monoterpenoids cause insect mortality by inhibiting acetylcholinesterase enzyme activity . Substituted phenols possess also insecticidal activities and could be better toxicants than monoterpenes .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Monoterpenoids and sesquiterpenoids have been reported to possess biological activities against pests such as Tribolium castaneum , Lasioderma serricorne or Attagenus piceus . Although their mode of action has not been well studied, some experiments have demonstrated that monoterpenoids cause insect mortality by inhibiting acetylcholinesterase enzyme activity . Substituted phenols possess also insecticidal activities and could be better toxicants than monoterpenes .…”
Section: Resultsmentioning
confidence: 99%
“…[39] [40] Although their mode of action has not been well studied, some experiments have demonstrated that monoterpenoids cause insect mortality by inhibiting acetylcholinesterase enzyme activity. [37][41] [42] Substituted phenols possess also insecticidal activities and could be better toxicants than monoterpenes. [3] The phenylpropanoids elemicin and myristicin possess anti-cholinergic activity.…”
Section: Insecticidal Properties Of Peperomia Borbonensis Essential Omentioning
confidence: 99%
“…Previous studies have demonstrated that lemongrass could effectively inhibit α-amylase and α-glucosidase activity [108]. For example, α-amylase inhibitory activity of the essential oil of lemon grass, for which linalool is the main active constituent, was found to be fifteen times higher compared to the currently used glucose lowering drug acarbose [109], while the inhibitory activity of methanol extract of lemon grass on α-glucosidase was more than 50% [108].…”
Section: Monoterpenes In Diabetesmentioning
confidence: 99%
“…It has been recently discovered that B. ligulata exhibit an insecticidal property. The volatile oil from roots of B. ligulata containing 1,8-cineole (119) 50%] was tested for its insecticidal activity against Drosophila melanogaster, which was found to be significant [109]. Thus, volatile oil from Bergenia species or its specific component could be deployed as a natural insecticidal agent [24,109].…”
Section: Insecticidal Activitymentioning
confidence: 99%